Valorisation of industrial wastes on hybrid low embodied carbon cement based mortars - Abdollahnejad, Zahra (2017)
Waste reuse is crucial in a context of a circular economy and zero waste sustainable needs. Some wastes like fly ash and waste soda lime silicate glass deserve an especial attention because they are generated in high amount and have a very low reuse rate. This paper reports results of  32 hybrid cement based mortars based on fly ash and waste glass. Showing the influence of mix design on the cost and the embodied carbon. The embodied carbon data for all constituents was taken from the database Ecoinvent. The results show that the reduction on the sodium hydroxide concentration and the activator/binder ratio led to lower embodied carbon. The results also show that a mixture of 80 percent fly ash, 10 percent waste glass and 10 percent calcium hydroxide activated with a 4M concentration sodium hydroxide solution has the lower embodied carbon (70 KgCO2e).